White light - Armstrong, Campbell (New York : William Morrow & Company, Inc., 1988)
Uncovering an international conspiracy aimed at destroying Soviet glasnost, Scotland Yard investigator Frank Pagan risks his life to prevent an air strike on Moscow and uprisings throughout Eastern Europe.
Keywords: LITERATURE -- FICTION